2007
DOI: 10.1007/978-3-540-74456-6_15
|View full text |Cite
|
Sign up to set email alerts
|

Linear Circuits, Two-Variable Logic and Weakly Blocked Monoids

Abstract: Following recent works connecting two-variable logic to circuits and monoids, we establish, for numerical predicate sets P satisfying a certain closure property, a one-to-one correspondence between F O[<, P]-uniform linear circuits, two-variable formulas with P predicates, and weak block products of monoids. In particular, we consider the case of linear TC 0 , majority quantifiers, and finitely typed monoids. This correspondence will hold for any numerical predicate set which is F O[<]-closed and whose predica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In [7] it was shown that a certain restricted version of the block product of our constant size circuit classes would actually yield linear size circuit classes (over the same base). Here having equations for all languages captured by this circuit class, not just the regular ones, would pay off greatly.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In [7] it was shown that a certain restricted version of the block product of our constant size circuit classes would actually yield linear size circuit classes (over the same base). Here having equations for all languages captured by this circuit class, not just the regular ones, would pay off greatly.…”
Section: Resultsmentioning
confidence: 97%
“…In the last section, we introduced bases for circuits that were defined by a variety of languages. Here we will define an unary operation · P arb on varieties mapping a variety of commutative regular languages V to the variety of languages V P arb recognized by constant size circuits over the base V. This rather strange looking notation comes from the algebraic background where similar ideas have been used on the algebraic side in [7]. Using the algebraic tools from that paper one could show that constant size circuit families recognize the same languages as the finitely typed groups in the block product V P arb , where V are the (typed) monoids corresponding to the gate types and P arb are the typed monoids corresponding arbitrary predicates and hence to the non-uniform wiring of the circuit family.…”
Section: The Block Product For Varieties Of Languagesmentioning
confidence: 99%
“…A survey dedicated to the class DA and its numerous appearances can be found in [76]. See [73,77] for FO with modular quantifiers, or [7,31] for applications of FO in circuit complexity, or [9] for FO over words with data. A decomposition technique in terms of so-called block products for monoids in DA has been introduced in [72].…”
Section: Remark 1 Sometimes Da Is Given By the Identity (Uv) U V (Uv)mentioning
confidence: 99%